2019
DOI: 10.1126/science.aaw2796
|View full text |Cite
|
Sign up to set email alerts
|

Generation of solar spicules and subsequent atmospheric heating

Abstract: Spicules are rapidly evolving fine-scale jets of magnetized plasma in the solar chromosphere. It remains unclear how these prevalent jets originate from the solar surface and what role they play in heating the solar atmosphere. Using the Goode Solar Telescope at the Big Bear Solar Observatory, we observed spicules emerging within minutes of the appearance of opposite-polarity magnetic flux around dominant-polarity magnetic field concentrations. Data from the Solar Dynamics Observatory showed subsequent heating… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 151 publications
(156 citation statements)
references
References 85 publications
6
149
1
Order By: Relevance
“…In addition, given the increasing evidence for the presence of unresolved minority polarities in the photosphere (e.g., Solanki et al 2017;Smitha et al 2017), such ejections resulting from flux cancellation can give rise to jet-like features found inside plages and strong network associated with the unresolved underlying minority polarities (Wang 2016;Wang et al 2019). We expect that other small-scale phenomena, such as spicules, could be associated with reconnection at lower atmospheric heights between converging cancelling polarities, and can potentially be associated with the cool outflows predicted from our model for different values of parameter space (e.g., Samanta et al 2019).…”
Section: Discussionmentioning
confidence: 86%
“…In addition, given the increasing evidence for the presence of unresolved minority polarities in the photosphere (e.g., Solanki et al 2017;Smitha et al 2017), such ejections resulting from flux cancellation can give rise to jet-like features found inside plages and strong network associated with the unresolved underlying minority polarities (Wang 2016;Wang et al 2019). We expect that other small-scale phenomena, such as spicules, could be associated with reconnection at lower atmospheric heights between converging cancelling polarities, and can potentially be associated with the cool outflows predicted from our model for different values of parameter space (e.g., Samanta et al 2019).…”
Section: Discussionmentioning
confidence: 86%
“…Because of this, information on the magnetic field of the whole atmosphere is required to study the interplay between the solar plasma and magnetic field. However, routine and reliable measurements of the solar magnetic field have only been achieved at the photospheric level (e.g., [1,2]). We still do not have a precise knowledge of the magnetic field in the upper solar atmo-sphere, especially the corona, which impedes our complete understanding of a wide range of phenomena including the solar cycle, solar eruptions and heating of the coronal plasma.…”
Section: Introductionmentioning
confidence: 99%
“…These jets appear to originate 2-3 Mm above the limb, which roughly places them at the top of H α RBEs. Samanta et al (2019) identified magnetic flux cancellations at the footpoint of some analyzed RBEs. Two events considered in the present study do exhibit morphological features and evolutionary pattern consistent with the flux cancellation scenario.…”
Section: Summary and Discussionmentioning
confidence: 97%